(untitled) (Journal of Nepal Geological Society, 2001)
The estimation of crystallinity and relative amount of clay minerals in the Kathmandu Basin sediments were made by using decomposition procedure of X-ray diffraction (XRD) patterns. Based on this study an attempt has been made to reconstruct the palaeoclimatic variation recorded in the clay minerals. The variations of the two illite crystallinity indices, Lanson index (LI) and modified Lanson index (MLI) of the drill-core sediments between 5 m and 49 m depth are linked to those of the relative amount of smectite to illitie minerals or to chlorite. The relative amount of kaolinite to illitic minerals or to chlorite roughly showed mirror image of the relative amount of smectite to illitie minerals or chlorite, respectively. The variation of the hydrolysis condition inferred from these indices were congruous with the variation of δ18O from planktonic foraminifers of deep sea sediments in the Arabian Sea, confirming that the climatic variations during the last 450 kyr in the Kathmandu Basin were closely related to global climate, without apparent local climatic changes. In addition, they depicted that it was dry during the cold climate and wet during the warm climate in the Kathmandu Basin.